The Effect of Mystery Box Learning Media on Science Learning Outcomes of Grade III Elementary School Students: Mystery Box Learning Media for Elementary Science Learning - Amala Nurlika Putri; Dya Ayu Agustiana Putri (Primary Education Insight, 2026)
The background of this study is the lack of use of interesting learning media, which causes low student learning outcomes. The purpose of this study is to determine the effect of the use of Mystery Box learning media on elementary school students' learning outcomes. This type of research uses a quantitative approach with a quasi-experimental design with a Nonequivalent Control Group design. The subjects of this study were 48 students divided into a control class and an experimental class. The tested data analysis technique produced a Cronbach's Alpha of 0.928, which means that the research instrument shows a very good level of reliability. The data were analyzed using a t-test with the results of the study, the t-value was 0.078 with degrees of freedom (df) 46.0 and p-value = 0.078. This p-value greater than 0.05 indicates that there is no significant difference between the average scores of the control group and the experimental group before the intervention, so that both groups are in a balanced initial condition. Meanwhile, in the posttest, the t-value was -13.31 with df 46.0 and p-value <0.001 indicating a significant difference between the control and experimental groups after the intervention. A negative t-value indicates that the average score of the experimental group is higher than the control group. This confirms that the use of Mystery Box learning media has a significant influence on the learning outcomes of elementary school students.